Smart Safety Belt Design to Avoid Accidents in Hazardous Industrial Environment - Muhammad Yaseen; Saad Qasim Khan; Muhammad Khurram; Rana N. Mubarak (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
Warehouse is one of the most dangerous places to work because of many potential dangers. The accidents caused by heavy vehicles result in seriousinjuries and even death. This paper proposes a solution to this problem. When a worker happens to be in any of such hazardous situations inside or outside workplace, he will press the emergency button (or pull a magnetic cord) placed in the smart safety belt which will not only stop the vehicles within 15 meters circle but also inform the workers within 250 meters circle through an indicator. In this technical paper, the outcome of first design phase has been reported. In the first design phase, we have successfully implemented a reliable and accurate ranging mechanism with ±0.3m maximum error. This ranging mechanism is based on wellknown RF Time-of-Flight (TOF) method. The maximum achievable transmit range of this solution is 300m.